Moral Intuitions and Pathological Personality Traits in Young Adults Sample - Kabziński, Paweł; Śliwerski, Andrzej (Przegląd Psychologiczny, 2025)
Objectives: The aim of this study was to examine whether a person’s pattern of moral intuitions, as understood according to Haidt and Graham’s theory, is associated with the severity of dysfunctional personality traits (according to ICD-11 criteria) in individuals aged 18–35. Method: The study involved a group of 272 people (195 women, 75 men, 2 people did not specify their sex) with an average age of 24,93 years. 65 people declared that they have a diagnosis of mental disorder. The following measures were used in the study: Moral Foundations Questionnaire (MFQ-PL) and Personality Inventory for ICD-11 (PiCD). Results: Moral intuitions from Care dimension were related to the severity of all dimensions of dysfunctional personality. The strongest correlations were observed for the relationship between Care and the Dissociality trait domain. The Loyalty foundation was identified as the second predictor of the severity of Dissociality traits. With regard to the Disinhibition dimension, the foundations of Care, Loyalty, and Authority turned out to be its predictors, while for the Anankastia trait domain, it was Fairness and Purity. Significant differences in the strength of the relationships and the statistical significance were observed for certain moral intuitions in comparisons between people declaring presence of a mental disorder and people without a current psychiatric diagnosis. Conclusions: The results of the study suggest that moral intuitions are associated with the severity of pathological personality traits in all domains. Moral intuitions from Care and Loyalty foundations predict the severity of trait domains to a greater extent than other moral intuitions, especially within the group of people with a current diagnosis of mental disorder.